The advance of the desert: battle-lines are being drawn - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
For nearly 20 years the Sahel has been suffering terrible drought. Despite many projects and heavy investment, the desert continues its inexorable advance on agricultural land, and seems to be invincible. Recently Segou in Mali was the venue for...